Bench and initial preclinical results of a novel 8 mm diameter double opposed helical biodegradable stent. Issue 6 (29th July 2016) - Herbert, Carrie E.; Veeram Reddy, Surendranath; Welch, Tré R.; Wang, Jian; Richardson, James A.; Forbess, Joseph M.; Nugent, Alan W.
Abstract : Background: Metallic endovascular stents are utilized off‐label in congenital heart disease. Biodegradable stents (BDS) offer potential advantages in a growing child. We have previously reported double opposed helical (DH) BDS up to 6 mm diameter (DH‐6). The objectives are to investigate the bench characteristics of larger 8 mm diameter BDS (DH‐8) manufactured with increasing strut thicknesses and the inflammatory profile in a porcine model. Methods: DH‐8 were manufactured with strut thicknesses 0.10, 0.12, and 0.18 mm and mechanical testing performed. Stents were deployed into the infrarenal descending aorta (DAO) of nine minipigs. At insertion (nonsurvival = 2), 1 week ( n = 2), 1 month ( n = 2), and 9 months ( n = 3) follow‐up angiography, intravascular ultrasound and histopathology were performed. Results: There was superior recoil and collapse pressure with increasing strut thickness, with 0.18 mm having 1.0% elastic recoil and collapse pressure 0.75 Atmospheres. There was good wall apposition at insertion with 5 BDS (4 DH‐8 and 1 DH‐6) but suboptimal in 4 as the minipigs infrarenal DAO were >8 mm (deployed at iliac bifurcation). Structural integrity was maintained in 8 BDS with 1 DH‐8 collapsed at 9 months, secondary to strut damage at insertion. No thrombosis was seen. There was mild inflammation and neointimal proliferation at 1 week and 1 month, but a moderate inflammatory response at 9 months. Conclusions: DH‐8 with increased strut thickness had acceptable mechanical properties at the cost of an increased inflammatory response. Miniaturization to improve delivery and further investigation on the long‐term inflammatory profile of thicker struts, including through degradation, is needed. © 2016 Wiley Periodicals, Inc.